Modeling larval dispersal for the gilthead seabream in the northwestern Mediterranean Sea. (December 2019) - Lett, Christophe; Barrier, Nicolas; Ourmières, Yann; Petit, Cécile; Labonne, Maylis; Bourjea, Jérôme; Darnaude, Audrey M.
Abstract: To investigate dispersal and connectivity between spawning and lagoon nursery habitats of the gilthead seabream, Sparus aurata, in the Gulf of Lions (northwestern Mediterranean Sea), we modeled the potential transport of the species' larvae between its supposed main spawning site in the region (the Planier Island) and two of its main local nursery areas (the coastal lagoons of Thau and Salses-Leucate). Passive larval drift simulations using a dispersal biophysical model showed a large variability in the possible trajectories from spawning to nursery areas and in the predicted ages for larvae arrival on the two nursery sites. The most common ages at arrival obtained in the simulations (20–60 days) are broadly consistent with previous modeling studies but contrast with the actual ages of the S. aurata post-larvae collected in 2016 and 2017 at time of the lagoon entrances (60–90 days, from otolith readings). The period between 25 and 70 days being critical for gilthead seabream larvae to acquire sufficient swimming, osmoregulatory, and olfactory abilities to enter coastal lagoons, we argue that ontogenic development plays a crucial role in the transport and local retention of S. aurata larvae in the studied region, explaining the discrepancy between simulation results and observed data. Highlights: We simulated dispersal and connectivity of the gilthead seabream in the Gulf of Lions. We estimated ages of larvae collected at the lagoon entrances from otolith readings. The most common ages at lagoon arrival obtained in the simulations are 20–60 days. The actual ages of collected larvae at time of the lagoon entrances are 60–90 days. Ontogenic development of seabream larvae likely explains this discrepancy.